Mechanisms Responsible for Genetic Hypertension in Schlager BPH/2 Mice - Jackson, Kristy L.; Head, Geoffrey A.; Gueguen, Cindy; Stevenson, Emily R.; Lim, Kyungjoon; Marques, Francine Z. (Frontiers in Physiology, 2019)
It has been 45 years since Schlager used cross bred mice to develop inbred strains with high, normal and low blood pressure (BPH/2, BPN/3 and BPL/1 respectively). The review covers the studies that have characterized and explored the mechanisms associated with the hypertension to take stock of exactly what is known and what remains to be determined. Growing evidence supports the notion that the mechanism of hypertension in BPH/2 mice is predominantly neurogenic with some of the early studies showing aberrant brain noradrenaline levels in BPH/2 compared with BPN/3. Analysis of the adrenal gland using microarray suggested an association with the activity of the sympathetic nervous system. Indeed, in support of this, there is a larger depressor response to ganglion blockade which reduced blood pressure in BPH/2 mice to the same level as BPN/3 mice. Greater renal tyrosine hydroxylase staining and greater renal noradrenaline levels in BPH/2 mice suggests sympathetic hyperinnervation of the kidney. Renal denervation reduced the blood pressure in BPH/2 but not BPN/3 mice, confirming the importance of renal sympathetic nervous activity contributing to the hypertension. Further there is an important contribution to the hypertension from miR-181a and renal renin in this strain. BPH/2 mice also display greater neuronal activity of amygdalo-hypothalamic cardiovascular regulatory regions. Lesions of the medial nucleus of the amygdala reduced the hypertension in BPH/2 mice and abolished the strain difference in the effect of ganglion blockade, suggesting a sympathetic mechanism. Further studies suggest that aberrant GABAergic inhibition may play a role since BPH/2 mice have low GABAA receptor δ, α4 and β2 subunit mRNA expression in the hypothalamus, which are predominantly involved in promoting tonic neuronal inhibition. Allopregnanolone, an allosteric modulator of GABAA receptors, which increase the expression of these subunits in the amygdala and hypothalamus, is shown to reduce the hypertension and sympathetic nervous system contribution in BPH/2 mice. Thus far, the evidence suggests that BPH/2 mice have aberrant GABAergic inhibition which drives neuronal overactivity within amygdalo-hypothalamic regions. This overactivity is responsible for the greater sympathetic contribution to the hypertension in BPH/2 mice, thus making this an ideal model of neurogenic hypertension.